2013
DOI: 10.1128/mbio.00716-13
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct N-Glycosylation Pathways Process the Haloferax volcanii S-Layer Glycoprotein upon Changes in Environmental Salinity

Abstract: N-glycosylation in Archaea presents aspects of this posttranslational modification not seen in either Eukarya or Bacteria. In the haloarchaeon Haloferax volcanii, the surface (S)-layer glycoprotein can be simultaneously modified by two different N-glycans. Asn-13 and Asn-83 are modified by a pentasaccharide, whereas Asn-498 is modified by a tetrasaccharide of distinct composition, with N-glycosylation at this position being related to environmental conditions. Specifically, N-glycosylation of Asn-498 is detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
95
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(97 citation statements)
references
References 35 publications
2
95
0
Order By: Relevance
“…While the absence of aglG, aglI, and aglE compromised pentasaccharide assembly, as expected, such deletions had no effect on the appearance of the low-salt tetrasaccharide attached to S-layer glycoprotein Asn-498 when cells were grown in medium with reduced salinity (95). It can thus be concluded that a novel N-glycosylation pathway is involved in the assembly of the tetrasaccharide N-linked to S-layer glycoprotein Asn-498.…”
Section: A Second N-glycosylation Pathway In Hfx Volcaniisupporting
confidence: 66%
See 1 more Smart Citation
“…While the absence of aglG, aglI, and aglE compromised pentasaccharide assembly, as expected, such deletions had no effect on the appearance of the low-salt tetrasaccharide attached to S-layer glycoprotein Asn-498 when cells were grown in medium with reduced salinity (95). It can thus be concluded that a novel N-glycosylation pathway is involved in the assembly of the tetrasaccharide N-linked to S-layer glycoprotein Asn-498.…”
Section: A Second N-glycosylation Pathway In Hfx Volcaniisupporting
confidence: 66%
“…To determine whether AglB is also involved in delivering the low-salt tetrasaccharide to S-layer glycoprotein Asn-498 when cells are grown under low-salinity conditions, the N-glycosylation profile of the S-layer glycoprotein in a strain lacking AglB was assessed by mass spectrometry. Such analysis revealed peaks corresponding to the S-layer glycoprotein-derived Asn-498-containing peptide to be modified by the low-salt tetrasaccharide as well as by its precursors (95), indicating that AglB is not the OST responsible for transferring this glycan from DolP to S-layer glycoprotein Asn-498. Consequently, a currently unidentified OST seems to serve this role.…”
Section: A Second N-glycosylation Pathway In Hfx Volcaniimentioning
confidence: 99%
“…sibly as-yet unidentified AglB genes with very low sequence homology, or even functionally homologous enzymes (41). Archaea produce multiple LLOs containing a variety of oligosaccharide and dolichol structures in one organism, and multiple AglB enzymes expressed in either a constitutive or inducible manner to use these LLOs.…”
Section: Discussionmentioning
confidence: 99%
“…This could account for the differences in intensity, observed in the protein gels. In order to test this hypothesis, we compared the glycans associated with the S-layer glycoprotein, a very abundant membrane protein that has been extensively used as a model to study protein glycosylation (20) in H. volcanii. We show, for the first time, the presence of N-linked oligosaccharides hydrolyzed by PNGase F in the S-layer glycoprotein of H. volcanii, because after the enzymatic treatment, the HPAEC-PAD profile clearly showed the presence of released oligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in response to changes in environmental salinity, H. volcanii modulates not only the N-linked glycans decorating the S-layer glycoprotein but also the sites of such posttranslational modification (19). Recently, it has been reported that two different glycosylation pathways participate in the synthesis of the tetra-and pentasaccharide (20).…”
mentioning
confidence: 99%